1994
DOI: 10.1002/ijc.2910570223
|View full text |Cite
|
Sign up to set email alerts
|

Cytoreductive effects of anti‐transferrin receptor immunotoxins in a multicellular tumor spheroid model

Abstract: We have evaluated the sensitivity to immunotoxins (IT) of monolayer and of 200-250 microns multicellular tumor spheroid (MTS) cultures obtained with human breast (MCF7) and glioblastoma (U118) tumor cells and with rat glioblastoma (9L) cells. Monolayer MCF7 and U118 cells were highly sensitive to antitransferrin receptor (anti-TfnR) ricin A chain (RTA)-IT (Tfn-RTA and MAb OKT9-RTA) treatment in the presence of the intracellular RTA-IT enhancing agent human serum albumin-monensin (HSA-Mo) conjugate. A 790- to 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
0

Year Published

1998
1998
2013
2013

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 12 publications
2
9
0
Order By: Relevance
“…Low or no expression of the TfR is unlikely to explain the result seen with 9L, which has been successfully treated with an anti-TfR immunotoxin (38). Instead, these findings are consistent with previous studies showing that hematopoietic cells are generally more sensitive to the antiproliferative effects of anti-TfR monoclonal Abs than other cell types (43).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Low or no expression of the TfR is unlikely to explain the result seen with 9L, which has been successfully treated with an anti-TfR immunotoxin (38). Instead, these findings are consistent with previous studies showing that hematopoietic cells are generally more sensitive to the antiproliferative effects of anti-TfR monoclonal Abs than other cell types (43).…”
Section: Discussionsupporting
confidence: 88%
“…Anti-rat TfR IgG3-Av contains the variable regions of the mouse monoclonal Ab OX26, which binds specifically to the rat TfR without blocking Tf binding (6). Chemical conjugation of OX26 with recombinant ricin A chain yielded an immunotoxin exhibiting strong inhibition of protein synthesis in Y3-Ag1.2.3, NBT II, and 9L cell lines (38,39). These findings suggested that anti-rat TfR IgG3-Av could be used to deliver molecules into rat cancer cells through receptor-mediated endocytosis, and we have now demonstrated that anti-rat TfR IgG3-Av can deliver different biotinylated molecules into Y3-Ag1.2.3 cells.…”
Section: Discussionmentioning
confidence: 99%
“…This distribution is likely to depend on the cell line and receptor type. A 50% reduction in the average number of transferrin binding sites in MTS as compared to monolayers was reported for 9L cells (Chignola et al, 1994), similar to the reduction we calculate for our system. No such reduction was found in MCF7 cells (Chignola et al, 1994), however, indicating that the effect of geometry on receptor distribution is not universal to all cell lines.…”
Section: Discussionsupporting
confidence: 78%
“…Chignola et al (1994) reported that antitransferrin receptor-ricin A conjugates were only slightly less toxic to 9L MTS than to 9L monolayers, but were much less toxic to MCF7 MTS than MCF7 monolayers. These Figure 9.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation